Adaptation Experiences on the Head Nurse’s Position, Buddhachinaraj Phitsanulok Hospital. - pingwong, sumlee; Boonpracom, Roongtiva; Wannapornsiri, Chommanard (NU Journal of Nursing and Health Sciences, 2025)
This qualitative research aimed to study the adaptation experiences in the position of head nurses, as well as the facilitating and hindering factors that affected these experiences at Buddhachinaraj Phitsanulok Hospital. Key informants were thirteen head nurses who were selected by purposive sampling. Data collection methods included in-depth interview, non-participatory observation, and field notes. Content analysis by Leonard method was employed in data analysis. The results of this study revealed six main themes regarding adaptation experiences in the position of head nurses: 1) Mindset adjustment, which involved striving to do one’s best, inspiring others through positive thinking, and being more accepting and receptive to others’ opinions. 2) Additional knowledge acquisition, by seeking management, academic, and technological knowledge. 3) Managing stressors by engaging in relaxation activities, seeking counseling, and participating in religious rituals. 4) Creating a beneficial self-image by projecting an external image of personality and good conduct sach as generosity, maturity. 5) Time management by planning work tasks and allocating time for personal life. and 6) Taking care of one’s health by nurturing both body and mind. The facilitating factors were organizational support and family support, while obstacles included responding to the needs of a multidisciplinary care team and disruptive technologies. The results of this research nursing administrators with a guideline for preparing new head nurses, focusing on the six identified themes, and promoting facilitating factors while addressing obstacles to enhance adaptation experiences for those entering the position of head nurse.